Association of chronic obstructive pulmonary disease and hemorrhoids: A nationwide cohort study. Issue 10 (March 2017) - Lin, Lih-Hwa; Siu, Justin Ji-Yuen; Liao, Po-Chi; Chiang, Jen-Huai; Chou, Pei-Chi; Chen, Huey-Yi; Ho, Tsung-Jung; Tsai, Ming-Yen; Chen, Yung-Hsiang; Chen, Wen-Chi
Abstract : Abstract: According to traditional Chinese medicine (TCM) theory, a specific physiological and pathological relationship exists between the lungs and the large intestine. The aim of this study is to delineate the association of chronic obstructive pulmonary disease (COPD) and hemorrhoids in order to verify the "interior–exterior" relationship between the lungs and the large intestine. A retrospective cohort study is conceived from the National Health Insurance Research Database, Taiwan. The 2 samples (COPD cohort and non-COPD cohort) were selected from the 2000 to 2003 beneficiaries of the NHI, representing patients age 20 and older in Taiwan, with the follow-up ending on December 31, 2011. The COPD cohort (n = 51, 506) includes every patient newly diagnosed as having Chronic Obstructive Pulmonary Disease (COPD, ICD-9-CM: 490–492, 494, 496), who have made at least 2 confirmed visits to the hospital/clinic. The non-COPD cohort (n = 103, 012) includes patients without COPD and is selected via a 1:2 (COPD: non-COPD) matching by age group (per 5 years), gender, and index date (diagnosis date of COPD for the COPD cohort). Compared with non-COPD cohorts, patients with COPD have a higher likelihood of having hemorrhoids and the age-, gender- and comorbidies-adjusted hazard ratio (HR) for hemorrhoids is 1.56 (95% confidence intervals [CI]:1.50–1.62). The adjusted HR of hemorrhoids for females is 0.79 (95% CI: 0.77–0.83), which is significantly less than that for males. The elderly groups, 40 to 59 years and aged 60 or above, have higher adjusted HRs than younger age groups (20–39 years), 1.19 (95% CI: 1.14–1.26), and 1.18 (95% CI: 1.12–1.24), respectively. Patients with COPD may have a higher likelihood to have hemorrhoids in this retrospective cohort study. This study verifies the fundamental theorem of TCM that there is a definite pathogenic association between the lungs and large intestine.